Pelatihan Calistung untuk Meningkatakan Budaya Literasi Pada Warga Lamakkaraseng Kecamatan Ulaweng - Andi Trisnowali MS; Sartika Arifin; Aprisal Aprisal (Rengganis Jurnal Pengabdian Masyarakat, 2022)
Literacy culture is very important to improve the quality of education in both rural and urban areas. Lamakkaraseng Village, Ulaweng District has a low literacy culture because there are residents who are not yet proficient in reading, writing or arithmetic. The Service Team conducted Calistung training activities (reading, writing, and arithmetic) for the villagers of Lamakkaraseng to improve their Literacy culture. The results obtained are that the participants' reading and writing skills as well as numeracy skills have improved, and some residents have started to get used to reading every day when they see the writings displayed around them. In addition, they are satisfied with the training activities carried out by the community service team